Comparison of neutrophil-to-lymphocyte, platelet-tolymphocyte, and monocyte-to-lymphocyte ratios in patients with schizophrenia, bipolar disorder, and major depressive disorder - Çatak, Zekiye; Üzmez, Emel; Öztürk, Nefise; Uğur, Kader (My University, 2018)
Objectives: It is thought that the immune system may play a role in the etiopathogenesis of many psychiatric andneurological diseases. In recent years, it was suggested that the neutrophil-to-lymphocyte, platelet-to-lymphocite, andmonocyte-to-lymphocyte ratio (neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), respectively) analysis is used to predict peripheral inflammation. Therefore, we aimedto compare the changes in NLR, PLR, MLR values in patients with schizophrenia, bipolar disorder, and depression.Methods: In this retrospective study, a total of 1543 inpatients/outpatients with a diagnosis of schizophrenia, bipolardisorder, and depression admitted to a mental health hospital between 2016 and 2017 were evaluated. Eighty controlsubjects were included from the hospital. All groups (schizophrenia, bipolar, depression, controls) were compared withone another in terms of NLR, PLR, and MLR values using SPSS 21.Results: There was significant difference in NLR between the schizophrenia group and healthy controls (p=0.007).When the patient groups (schizophrenia, bipolar disorder, and depression groups) were compared with each other,NLR values were significantly higher in patients with schizophrenia compared to depression groups (p<0.001). MLR valuesfor the schizophrenia and bipolar disorder groups were significantly higher than for the depression group (p=0.001and p<0.001, respectively). PLR values were found to be significantly higher in patients with schizophrenia than inpatients with bipolar disorder (p=0.007).Conclusion: The changes in NLR, PLR, and MLR values used as indicators of inflammation have shown that psychiatricdisorders are associated with inflammatory processes. However, it was observed that this relationship was more obviousin schizophrenia compared to bipolar disorder and depression.
Keywords: Psikiyatri